2020
DOI: 10.3390/ijerph17124318
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of WTC-Particulate Matter and Lysophosphatidic Acid Exposure and the Role of RAGE: In-Vitro and Translational Assessment

Abstract: World Trade Center particulate matter (WTC-PM)-exposed firefighters with metabolic syndrome (MetSyn) have a higher risk of WTC lung injury (WTC-LI). Since macrophages are crucial innate pulmonary mediators, we investigated WTC-PM/lysophosphatidic acid (LPA) co-exposure in macrophages. LPA, a low-density lipoprotein metabolite, is a ligand of the advanced glycation end-products receptor (AGER or RAGE). LPA and RAGE are biomarkers of WTC-LI. Human and murine macrophages were exposed to WTC-PM, and/or LPA, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 120 publications
(175 reference statements)
0
5
0
Order By: Relevance
“…WTCS cluster 2 was characterized by circulating inflammatory and remodeling markers including MMP1, 2, 3, 8, 12, 13, soluble receptors RAGE, IL-1RA, IL-6Ra, TNFRI, TNFRII, and chemokines IL-8, and CCL17. Many of these biomarkers, in particular MMP's and RAGE, have previously been reported to be very important to understand the responses in the WTC responders, signifying either a prediction of protection or worsening of lung function [18,[23][24][25][26]57]. Our data cannot predict lung function measured by spirometry because participants were enrolled based on normal spirometry measurements ( [5], Table 1).…”
Section: Discussionmentioning
confidence: 92%
“…WTCS cluster 2 was characterized by circulating inflammatory and remodeling markers including MMP1, 2, 3, 8, 12, 13, soluble receptors RAGE, IL-1RA, IL-6Ra, TNFRI, TNFRII, and chemokines IL-8, and CCL17. Many of these biomarkers, in particular MMP's and RAGE, have previously been reported to be very important to understand the responses in the WTC responders, signifying either a prediction of protection or worsening of lung function [18,[23][24][25][26]57]. Our data cannot predict lung function measured by spirometry because participants were enrolled based on normal spirometry measurements ( [5], Table 1).…”
Section: Discussionmentioning
confidence: 92%
“…Cases of WTC-OAD had either WTC-Lung Injury (WTC-LI; FEV 1 <LLN) and/or Airway Hyperresponsiveness (AHR;positive methacholine or positive bronchodilator testing) at any time point post-9/11 (N=921). (22)(23)(24)(25)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67) Cases of WTC-OAD were compared to N=3,094 without WTC-OAD at any time after 9/11.…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that distinct studies implicated LPA-RAGE interaction in lung, mammary and ovarian tumors (14, 15). Other studies suggested roles for LPA-RAGE in stroke (16) and upon exposure to World Trade Center particulate matter, the released LPA induced inflammation in macrophages, at least in part through RAGE (17).…”
Section: Lysophosphatidic Acidmentioning
confidence: 99%